A method to generate structural impulse-responses for measuring the effects of shocks in structural macro models - Andreas Beyer; Roger E. A. Farmer (European Central Bank (ECB), 2006)
We develop a technique for analyzing the response dynamics of economic variables to structural shocks in linear rational expectations models. Our work differs fromstandard SVARs since we allow expectations of future variables to enter structural equations. We show how to estimate the variance-covariance matrix of fundamental and non-fundamental shocks and we construct point estimates and confidence bounds for impulse response functions. Our technique can handle both determinate and indeterminate equilibria. We provide an application to U.S. monetary policy under pre and post Volcker monetary policy rules.
Keywords: C39; C62; D51; E52; E58; 330; Identification; indeterminacy; rational expectations models; Rationale Erwartung; VAR-Modell; Schock; Theorie